Congenital Neurological Disease Associated With HoBi-like Pestivirus Infection in a Newborn Dairy Calf From Brazil - Barreto, José Victor Pronievicz; Lorenzetti, Elis; Fritzen, Juliana Torres Tomazi; Jardim, Andressa de Melo; Oliveira, Thalita Evani Silva; Headley, Selwyn Arlington; Alfieri, Amauri Alcindo; Cunha Filho, Luiz Fernando Coelho da (Frontiers in Veterinary Science, 2022)
HoBi-like pestivirus (HoBiPeV) has been reported in several biological samples from cattle worldwide, but there are no descriptions of this virus associated with neurological symptoms. This report described the first occurrence of neurological disease associated with HoBiPeV in a newborn dairy calf. A mixed-breed Holstein calf had severe neurological symptoms at birth and died at 21 days old. Tissue fragments (central nervous system (CNS), myocardium, liver, kidney, lung, intestine, and spleen) were submitted to RT–PCR assay for the partial 5'-untranslated region (5'UTR) and N-terminal autoprotease (Npro) gene of the pestivirus genome, and CNS tissue fragments were submitted to histopathological and immunohistochemical evaluation. The RT–PCR assay indicated that kidney, CNS, and intestinal tissue fragments were positive for the pestivirus 5'UTR, and the CNS and intestinal tissue fragments were positive for the pestivirus Npro gene. Amplicons with high DNA quantification in the 5'UTR (CNS - cerebral cortex) and Npro (CNS - cerebral cortex and intestine) RT–PCR assays were sequenced. The nucleotide (nt) sequence and phylogenetic analysis of the 5'UTR strain exhibited 93.6 to 99.4%, 85%, 89.4 to 89.9%, 85.1%, and 90.5 to 91.5% nt identity with HoBiPeV strains from clades a, b, c, d, and e, respectively. The Npro amplicons showed 99.7% nt identity to each other and 90.4 to 96.5%, 85.1 to 85.3%, 79.2 to 79.7%, and 85.8 to 86.5% nt identity with HoBiPeV strains from clades a, c, d, and e, respectively. Histopathology revealed neuronal necrosis at the cerebrum, cerebellum, and brain stem. An immunohistochemical assay designed to identify antigens of bovine viral diarrhea virus antigens revealed positive intracytoplasmic immunoreactivity within neurons at the cerebral cortex, cerebrum, cerebellum, and spinal cord. Thus, this report provides information about the first identification of HoBiPeV in tissues of the CNS in a newborn dairy calf with neurological symptoms.